2014
DOI: 10.3390/bios4030301
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Biosensors for Organophosphate and Carbamate Pesticides: A Review

Abstract: Due to the great amount of pesticides currently being used, there is an increased interest for developing biosensors for their detection. Among all the physical transducers, piezoelectric systems have emerged as the most attractive due to their simplicity, low instrumentation costs, possibility for real-time and label-free detection and generally high sensitivity. This paper presents an overview of biosensors based on the quartz crystal microbalance, which have been reported in the literature for organophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 52 publications
0
51
0
1
Order By: Relevance
“…Ferroelectric materials have been used for many years in nonvolatile ferroelectric random access memories (FRAM) [1,2], microsensors and microactuators [3][4][5], as well as high frequency broadband filter applications [6]. This requires the growth of ferroelectric thin films on a (buffered) semiconducting substrate (e.g., silicon), usually with an interposing metal or conducting metal oxide layer as bottom electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Ferroelectric materials have been used for many years in nonvolatile ferroelectric random access memories (FRAM) [1,2], microsensors and microactuators [3][4][5], as well as high frequency broadband filter applications [6]. This requires the growth of ferroelectric thin films on a (buffered) semiconducting substrate (e.g., silicon), usually with an interposing metal or conducting metal oxide layer as bottom electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Tang et al demonstrated antigen-antibody interaction via GOD conjugated hollow gold-silver microspheres (AuAgHSs) further coupled using Prussian blue NPs (an artificial catalase), on a graphene-based immunosensor [117]. Pesticidal study [96] Hba1c biosensor Determining glycated hemoglobin [97] Piezoelectric biosensors Detecting carbamate and organophosphate [98] Uric acid biosensors Diagnosis of various clinical abnormalities or illness (e.g., diagnosis of cardiovascular disease) [99,100] Glucose oxidase electrode biosensors Measuring of glucose in biological sample of diabetic patient [101] Quartz-crystal biosensors Detection of proteins at ultrahigh-sensitive level in liquids [102] Optical Polyacrylamide based hydrogel biosensors Immobilization of biomolecules [30] Silicon biosensor For biosensing, bioimaging, and in cancer therapy [103,104] Microfabricated biosensor In novel drug delivery (e.g., in optical corrections) [105] Fluorescence tagged/Genetically encoded biosensor Investigation of various biological process and molecular systems in the cell [27,[106][107][108] Electrochemical or optical Nanomaterials biosensors For diagnosis and in drug delivery [32,93,[109][110][111][112][113][114] …”
Section: Glucose Monitoringmentioning
confidence: 99%
“…The use of biosensors for analytical purposes in food applications is increasing because of their simplicity, low cost, and easy handling. In particular, piezoelectric immunosensors are becoming an interesting alternative to classical immunoassays for pesticide detection as they offer the advantages of real‐time output, sensitivity, simplicity, and cost‐effectiveness, without the requirement of reagent labeling . We have recently developed piezoelectric immunosensors based on high fundamental frequency quartz crystal microbalance (HFF‐QCM) for the detection of pesticides and disease biomarkers .…”
Section: Introductionmentioning
confidence: 99%